Theories of integration : the integrals of Riemann, Lebesgue, Henstock-Kurzweil, and Mcshane - 525804 Kurtz, Douglas S.; Kurzweil, Jaroslav (New Jersey, NJ. : World Scientific)
Includes bibliographical references (p. 289-290) and index